HUMAN RESOURCE PLANNING IN THE INDUSTRIAL SECTOR STRATEGIES TO DEAL WITH TECHNOLOGICAL CHANGE AND GLOBAL COMPETITION - Muhammad Reyhan Yafi; Maulana Malik Ibrahim; Reno Fandika; Ray Agung Pangestu; Hadi Supratikta (PT. Jurnal Center Indonesia Publisher, 2025)
Human Resources (HR) plays a central role in determining the competitiveness and success of companies in the industrial sector. HR planning is becoming increasingly complex with technological disruption, globalization, and changing market dynamics. This article discusses in depth the importance of HR planning in the industrial sector by reviewing various aspects such as industrial environment analysis, identification of workforce needs, employee development strategies, and challenges faced. In addition, emphasis is also given to the strategies that companies need to take to improve the effectiveness of their HR management, especially in facing challenges in the digital and automation era. The conclusion emphasizes that adaptive and data-driven HR planning can help industrial companies maintain their competitiveness in the global market.